A Transparent Authentication and Distortion Measurement Technique for Images - Zhu, Bin Benjamin; Swanson, Mitchell D.; Tewfik, Ahmed H. (Proc. of IEEE Digital Signal Processing Workshop, 1996)
We propose a novel scheme to embed an invisible signature into an image to check image integrity and measure its distortion. The technique is based on the pseudo-noise sequences and visual masking effects. The values of an image are modified by a pseudo-noise signature which is shaped by the perceptual thresholds from masking effects. The method is robust and can gauge errors accurately up to half of the perceptual thresholds. It also readily identifies large image distortion. Experimental results after applying JPEG and white noise to the image are also reported